Determinants of Antenatal Care Utilization Among Childbearing Women in Burkina Faso - Badolo, Hermann; Bado, Aristide Romaric; Hien, Hervé; De Allegri, Manuela; Susuman, Appunni Sathiya (Frontiers in Global Women's Health, 2022)
Introduction: Antenatal care (ANC) is one of the pillars of maternal and child health programs aimed at preventing and reducing maternal and child morbidity and mortality. This study aims to identify the factors associated with ANC use, considering both health care demand and supply factors in the single analysis. Methods: We used data from the endline survey conducted to evaluate the impact of the performance-based financing program in Burkina Faso. Multilevel statistical techniques were used to examine individual and contextual effects related to health care demand and supply simultaneously and thus measure the relative contribution of the different levels to explaining factors associated with ANC use. Results: The working women were five times (OR: 5.41, 95% CI 4.36-6.70) more likely to report using ANC services than the women who were not working (OR: 5.41, 95% CI 4.36-6.70). Women living in a community with high poverty concentration were 32.0% (OR: 0.68, 95% CI 0.50-0.91) less likely to use ANC services than those in a community with low poverty concentration. Women living in a community with a medium concentration of women’s modern contraceptive use were almost twice (OR: 1.88, 95% CI 1.70-2.12) more likely to use ANC services than those living in a community with a low concentration of women’s modern contraceptive use. Women living in the health area where the level of ANC quality was high were three times (OR: 2.96, 95% CI 1.46-6.12) more likely to use ANC services than those in the health area where the ANC quality was low. Conclusion: Policies that increase the opportunity for improving the average ANC quality at the health facility, the level of women’s modern contraceptive use and women employment would likely be effective in increasing the frequency of use of antenatal services.